(untitled) (Texas Journal of Engineering and Technology, 2023)
the article examines the processes of ensuring the security of the database, the creation and research of the database of users of the protected corporate network, one of the important tasks in ensuring the security of the database of users of the corporate network is the provision of Information Integrity, models of ensuring security